ANALISA BIAYA PEMANENAN TANAMAN MANGIUM (Acacia mangium) DI PT BINA SILVA NUSA KECAMATAN BATU AMPAR KABUPATEN KUBU RAYA - Faqih, Septian; Hardiansyah, Gusti; Roslinda, Emi (Universitas Tanjungpura, 2018)
Harvesting of forest products is an unit between human components and equipment. These components are aimed at removing forest products in wood form from forest areas. This research was held in 2017 at PT Bina Silva Nusa, aimed at analyzing the amount of costs required for harvesting activities, including logging, skidding and hauling activities. This study data analysis method is collecting primary data in the field and secondary data is information obtained from related company. The cost of each aspect harvesting activities of forest products is processed in tabulation form and calculated to obtain production costs. The amount of costs that PT Bina Silva Nusa spend for timber harvesting activities which include logging, skidding, loading and transportation activities is Rp 138.774/m3. These costs are the sum of all costs spend by the company in each component of harvesting activities, including the cost of logging contracts of Rp 12.000/m3, skidding contract costs of Rp 85.000/m3, loading and unloading costs of Rp 17.500/m3, and transportation costs of Rp 15.874/m3, and also has been added with Forest Resource Provision issued by the company per m3 of timber Rp 8.400. The cost of harvesting acacia wood if all components are carried out independently is Rp 115.214/m3, while the details of the costs are Rp 11.250/m3 for logging, skidding Rp 65.555/m3, loading and unloading Rp. 14.135/m3 and hauling Rp 15.874/m3,with the same provision is Rp 8.400 / m3.Keywords: Felling, Harvesting, Hauling, Production Cost, Skidding,